Low fasting glucose and future risks of major adverse outcomes in people without baseline diabetes or cardiovascular disease: a systematic review and meta-analysis - Hsin-Chieh Yeh; Hung-Wei Liao; Jeffrey Saver; Chi-Hsin Sally Chen; Yi-Ling Wu; Meng Lee; Bruce Ovbiagele (BMJ Open)
Objective To investigate the link between low fasting blood glucose levels and all-cause mortality and cardiovascular outcomes among people without baseline diabetes or cardiovascular disease.Design Systematic review and meta-analysis.Data sources PubMed and Embase (1966–February 2019).Selection criteria Prospective cohort studies were included for meta-analysis if they reported adjusted HRs with 95% CIs for associations between risk of all-cause mortality, stroke, major cardiovascular events, coronary heart disease and low fasting glucose levels (<4.6 mmol/L and/or 4.0 mmol/L, respectively) versus normal fasting glucose levels.Data extraction and statistical analysis Two independent reviewers extracted data from eligible studies. Heterogeneity was assessed by p value of χ2 tests and I2. We assessed four characteristics for each included study based on items developed by the US Preventive Task Force, as well as the modified checklist used in previous studies.Results Eleven articles (consisting of 129 prospective cohort studies) with 2 674 882 participants without diabetes and cardiovascular disease at baseline were included in this meta-analysis. Pooled results from the random effects model showed increased risks of all-cause mortality (HR: 1.56; 95% CI 1.09 to 2.23), total stroke (HR: 1.08, 95% CI 1.03 to 1.13) and ischaemic stroke (HR: 1.06, 95% CI 1.01 to 1.10), and major cardiovascular events (HR: 1.05, 95% CI 1.03 to 1.07) among people with a fasting glucose <4.0 mmol/L, as compared with people with normal fasting glucose. The less stringent low fasting glucose level, <4.6 mmol/L, was not associated with increased risk of any endpoints.Discussion and conclusions Among people without baseline diabetes or cardiovascular disease, a fasting blood glucose level of <4.0 mmol/L is associated with increased risk of all-cause mortality, major cardiovascular events and stroke.